Trust in the investor relationship marketing of startups: a systematic literature review and research agenda - Manuel Kaiser; Elisabeth S. C. Berger (Management Review Quarterly, 2020)
An important task of entrepreneurs is the management of investor relations. Past literature has emphasized the role of trust for managing relationships and regulating their quality. However, the landscape of investors has changed due to digitalization, so that new players have joined and expanded the investor offer. Entrepreneurs also often enter into relationships with multiple investors, which can challenge investor relationship marketing. To provide an overview, we conduct a structured literature review on the entrepreneur's relationship marketing with four key investors: venture capitalists (VCs), business angels (BAs), banks, and crowd funders. The paper improves the understanding of trust as a concept in the management of investor relations and identifies directions for future research. The results show that research has predominantly studied trust in the VC–entrepreneur relationship. Across different investors, the primary focus has been on factors that influence trust building, especially investor communication and entrepreneur–investor fit. Furthermore, the results show that trust has an influence on cooperation by strengthening the relationship and reducing risk.
Keywords: G24; L26; M13; M31; 650; Entrepreneurial marketing; Entrepreneurial finance; Trust; Relationship marketing; Investor relations; Startup